2019
DOI: 10.3390/polym11040606
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Poly(N-Isopropylacrylamide-co-Dimethylaminoethyl Methacrylate) Microgel Aqueous Dispersions with Potential Antimicrobial Properties

Abstract: The work herein describes the preparation of thermoresponsive microgels with potential antimicrobial properties. Most of the work performed so far regarding microgels with antimicrobial activity, deals with the ability of microgels to carry and release antibiotics or antimicrobial agents (antimicrobial peptides). The originality of this work lies in the possibility of developing intrinsic antimicrobial microgels by copolymerization of the well-known thermoresponsive monomer, N-isopropylacrylamide (NIPAM) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Moreover, the temperature span of the phase transition becomes significantly smaller as the concentration of PEP increased. This result is in good agreement with reported studies on poly( N ‐ethylacrylamide) and poly( N ‐isopropylacrylamide) . Furthermore, the LCST can also be obtained by extrapolation of the curves of LCSTs for different polymer concentrations.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, the temperature span of the phase transition becomes significantly smaller as the concentration of PEP increased. This result is in good agreement with reported studies on poly( N ‐ethylacrylamide) and poly( N ‐isopropylacrylamide) . Furthermore, the LCST can also be obtained by extrapolation of the curves of LCSTs for different polymer concentrations.…”
Section: Resultssupporting
confidence: 91%
“…Two additional peaks around 1649 cm −1 , 1549 cm −1 were corresponding to the stretching vibration of C = O groups in amide functional groups and N-H bending vibration of amide groups in NIPAAm, respectively. The broad peak around 3451 cm −1 referred to the N-H stretching vibration of NIPAAm amide groups [47,48].…”
Section: Fourier Transforms Infrared (Ftir) Spectroscopymentioning
confidence: 99%
“…They studied their fractal structure and concluded that both salt concentration and temperature modify the interactions among microgels [8,43]. Recently, we also attempt to modify microgels colloidal behavior through quaternization but no relevant differences were obtained [44]. Therefore, to determine the flow behavior of the hybrid microgel dispersions and to understand how hybrid microgels interact within the aqueous dispersion could be as relevant as the characterization of their responsiveness.…”
Section: Resultsmentioning
confidence: 99%
“…These two scaling theories, which are an extension of the computer model proposed by Brown and Ball [45] are based on the fact that microgel dispersions are a collection of flocs–fractal objects closely packed throughout the sample-. These models were recently used to study the interactions occurring among poly(N-Isopropylacrylamide) polycationic microgels [44].…”
Section: Resultsmentioning
confidence: 99%